2011
DOI: 10.1590/s1519-70772011000200004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Lei 11.638/07 sobre o conservadorismo condicional das empresas listadas BM&FBOVESPA

Abstract: A Lei nº 11.638/07 alterou, substancialmente, as normas e práticas brasileiras de contabilidade e tais mudanças poderão ter impactos significativos no conservadorismo dos resultados contábeis divulgados. Conhecer o papel do conservadorismo e seus determinantes é importante para compreender a natureza, finalidade e implicações das estimativas contábeis. Este estudo teve como objetivo investigar se a promulgação da Lei n º 11.638/07 alterou o grau de conservadorismo contábil condicional de empresas brasileiras l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2
29

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 14 publications
(5 reference statements)
4
16
2
29
Order By: Relevance
“…The results regarding conservatism corroborated the findings of Santos et al (2011) and Rodrigues (2012), although the finding that this attribute was absent in the pre-IFRS period differs from other studies. This field of study merits examination beyond the descriptive nature of the econometric models used, which is the typical approach of research studies.…”
Section: Final Considerationssupporting
confidence: 88%
See 3 more Smart Citations
“…The results regarding conservatism corroborated the findings of Santos et al (2011) and Rodrigues (2012), although the finding that this attribute was absent in the pre-IFRS period differs from other studies. This field of study merits examination beyond the descriptive nature of the econometric models used, which is the typical approach of research studies.…”
Section: Final Considerationssupporting
confidence: 88%
“…In turn, Rodrigues (2012) found that the adoption of IFRS in Brazil did not increase conditional conservatism, partly corroborating Santos et al (2011), or affected the associative capacity of accounting profits (value relevance), thus contradicting the results of Lima (2010) and Costa (2012).…”
Section: Previous Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…The evidence gathered in this regard indicates that the associative capacity of accounting earnings should have improved (Lima, 2010Rodrigues, 2012. However, dimensions such as informational content, conservatism, timeliness and persistence should not have been impacted by the adoption of a new set of accounting standards (Lima, 2010, Rodrigues, 2012, Santos, Lima, Freitas, & Lima, 2011.…”
Section: Eps It+k P It-(1-k)mentioning
confidence: 99%